2014
DOI: 10.1590/0034-76121359
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of implementing Regulatory Impact Analysis in Brazil

Abstract: In an increasingly complex society, regulatory polices emerge as an important tool in public management. Nevertheless, regulation per se is no longer enough, and the agenda for a regulatory reform is increasing. Following this context, Brazil has implemented Regulatory Impact Analysis (RIA) in its regulatory agencies. Thus, Brazilian specificities have to be considered and, in this regard, a systematic approach provides a significant contribution. This article aims to address some critical reflections about wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
7
0
3
Order By: Relevance
“…However, regulation can have a high impact on society (DASKAL et al 2019) and needs to be adequately developed so that its objectives are achieved and unintended consequences are not produced (CASTRO, 2014;HASSAN, 2015).…”
Section: Regulation and Regulatory Impact Assessmentmentioning
confidence: 99%
“…However, regulation can have a high impact on society (DASKAL et al 2019) and needs to be adequately developed so that its objectives are achieved and unintended consequences are not produced (CASTRO, 2014;HASSAN, 2015).…”
Section: Regulation and Regulatory Impact Assessmentmentioning
confidence: 99%
“…A survey done in low-income countries showed that RIA has been applied but it is still in the early stage of adoption (Kirkpatrick et al, 2004). In Brazil, RIA is incipient and faces some problems to proper implementation, such as the lack of a centralized regulatory agency (Castro, 2014). Also, the lack of studies and information on this topic hampers the RIA application.…”
Section: Total Coliformsmentioning
confidence: 99%
“…In the Brazilian regulatory environment, since 2007, when the program for strengthening the institutional capacity of regulatory management (PRO‐REG in Portuguese) was created, some federal agencies have already been involved in the process of implementing RIA and some of its procedures (De Castro, ). However, PRO‐REG was later discontinued, and its changing locus has not promoted the debate on RIA at the federal level.…”
Section: Introductionmentioning
confidence: 99%